Artistic Interaction of Color and Composition in Alisher Navoi’s Works - Qutliyeva Mahbuba Bekpulatovna (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Abstract: This study explores the artistic interplay between color and composition in the works of Alisher Navoi. The research analyzes how color and compositional elements work together to create harmonious, aesthetically engaging, and emotionally expressive literary and visual imagery. Navoi’s works demonstrate a sophisticated balance between visual appeal, narrative structure, and symbolic meaning, where color reinforces compositional organization and enhances the emotional and thematic impact of artistic expression. The study also highlights pedagogical implications, showing how understanding the interaction of color and composition can develop students’ visual literacy and creative competencies.